Pengaruh Likuiditas, Kebijakan Hutang, Pertumbuhan Perusahaan dan Ukuran Perusahaan Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening pada Perusahaan Sub Sektor Farmasi Di Bursa Efek Indonesia Periode 2014 – 2019 - Suryanti Suryanti; Arna Suryani; Yunan Surono (Universitas Batanghari, 2021)
This study is to look at the influence of Liquidity, Debt Policy, Company Growth And Company Size on Company Value With Profitability As Intervening Variable In Pharmaceutical Sub-Sector Companies on Indonesia Stock Exchange Period 2014 - 2019. Liquidity variables that are diproxykan with current ratio, debt policy that is diproxykan with debt to equity ratio, growth of the company that is diproxykan with changes in total assets and the size of the company that is diproxykan with normal logarithm (Ln) sales to the value of the company that is mortgaged with price to book value with profitability diproxykan with return on equity as intervening variables. The research sample used is the Pharmaceutical Sub Sector on the Indonesia Stock Exchange during the 6-year observation period, starting from 2014 - 2019 recorded as many as 10 companies, which have a complete financial report and which have a complete research indicator report in the annual financial report during the research period as many as 8 companies. This study used purposive sampling and data analysis techniques using the help of microsoft Excell and SPSS 22.0 software. with Path Analysis. The results showed that; 1) Simultaneously all free variables have no effect on bound variables whereas that partially only the growth variables of the company are diproxykan with changes in total assets that affect the variable profitability. 2) Simultaneously all free variables have a significant effect on bound variables whereas partially only the growth variables of the company are diproxykan with changes in total assets that have no effect on the variable value of the company. 3) Variable profitability diproxykan with return on equity has no effect on the variable value of the company that is diproxykan with price to book value. 4) Variable liquidity, debt policy, company growth and the size of the company to the value of the company with profitability as an intervening variable has a total influence of 11.1838%, the large influence including weak.